Sister Carrie - Dreiser, Theodore, 1871-1945 (Open Road Integrated Media, Inc., 2016)
The controversial classic novel of a young woman's journey from poverty to stardom in capitalist America. Dissatisfied with life in rural Wisconsin, eighteen-year-old Carrie Meeber travels to Chicago. With no money or prospects, her only means of survival is a job in a squalid factory'until Charlie Drouet, a charming, well-dressed man, offers to take her to dinner. Lavishing her with gifts, fine clothes, and her own apartment, Charlie introduces Carrie to a life of wealth and sophistication far removed from the Victorian moralizing of her youth. But when Carrie begins an affair with another man'and a career as an actress'her ambitions and desires reach far beyond what Charlie, or any man, can offer. Later adapted into the Academy Award-nominated film Carrie, starring Laurence Olivier, Sister Carrie is widely considered "one of the landmark novels of the twentieth century" and a masterpiece of literary realism (The New York Times). But when it was first published in 1900, it stirred controversy for its depiction of female sexuality. In his Nobel Prize speech, Sinclair Lewis declared that "Sister Carrie ... 'ame to housebound and airless America like a great free Western wind, and to our stuffy domesticity gave us the first fresh air since Mark Twain and Whitman."This ebook has been professionally proofread to ensure accuracy and readability on all devices